'Futility' – let's put it out of its misery. Issue 1 (1st June 2011) - Saul, P
Abstract : Though still on life support, George improved when his infected leg was amputated above the knee. But his wife, Annette, pleaded with the surgeon to withdraw intensive care treatment. George had made her promise that she would never let him have an amputation. But who has the authority to make this choice? The surgeon believed it was the best medical practice to continue (as treatment was not 'futile'), but George very clearly had a preference, and Annette a responsibility to promote it. The concept of futility was introduced into this discussion to help resolve this dilemma (which rapidly became a dispute), and, as often happens, failed to produce a resolution. The notion of futility has been dissected in countless law courts, medical journals and standard textbooks of medical ethics for a generation. But much of the discussion has, ironically, proved futile and numbers of publications in this area is rapidly falling. I suggest that futility, as originally conceived in a medical setting, is no longer a valid concept, and, like euthanasia, is a term better abandoned than further debated. I suggest that, as in debates about 'best interests' (another term looking for a definition), all discussion eventually returns to what the patient or family might have seen as important. The very basis of futility, originally conceived as a medical judgement based on probabilities, has disappeared. I contend that we abandon the term, and instead invest in fair and transparent processes that maximise authentic and justifiable decisions.